CASH MANAGEMENT STRATEGY IN INCREASING COMPANY LIQUIDITY IN TIMES OF ECONOMIC CRISIS - Eka Septariana Puspa; Windy Permata Suyono (Adisam Publisher, 2025)
This research aims to analyze effective cash management strategies in increasing company liquidity during economic crises. Economic crises often cause high uncertainty, decreased market demand, and increased operational costs which affect company survival. Therefore, proper cash management is very important to ensure companies can still meet short-term financial obligations and maintain their operations. Based on existing literature studies, several cash management strategies that have proven to be effective include careful cash planning, strict management of receivables and payables, cutting operational costs, and efficient inventory management. This research also identifies key success factors, such as flexibility in cash management, diversification of financing sources, and the company's ability to adapt quickly to market changes. However, the company continues to face various challenges, such as difficulties in accessing external financing, decreasing revenues, and increasing credit risks which hinder optimal cash management. Thus, this research concludes that companies that can implement cash management strategies that are adaptive and responsive to market dynamics will have a greater chance of surviving and maintaining liquidity during the economic crisis.